Implemetasi profil pelajar Pancasila dalam proses pembelajaran pendidikan pancasila dan kewarganegaraan - A'yuniah*, Ivo Janatul; Damanhuri, Damanhuri; Nida, Qotrun (Universitas Syiah Kuala, 2024)
Learning is a process where an individual gains knowledge, skills, attitudes and values through interaction with the environment. So this research aims to find out how to implement the Pancasila student profile in the learning process starting from planning, implementing and evaluating the six indicators of the Pancasila student profile in the learning process. This research uses an approach with a descriptive study method with data collection techniques, namely observations carried out at SMP Negeri 1 Serang City, and interview techniques carried out with Civics teachers and class VII students at SMP Negeri 1 Serang City, and documentation techniques namely photos of implementation activities. the six dimensions of the Pancasila student profile. The results of research carried out in implementing the Pancasila student profile in the learning process are implemented where the key indicators are implemented in the learning process. It is hoped that the implementation of the Pancasila student profile will be able to create character education for students who require the role of all parties, both teachers and parents, to assist them in the learning process.